The Exploration of Challenges and Applications of Corpus Linguistics in the Compilation of Health-Related Local Wisdom Vocabulary - Hengsuko, Chatchanok (Journal of Roi Kaensarn Academi, 2024)
This study explores the challenges and applications of corpus linguistics in compiling a specialized English vocabulary list for health-related local wisdom. The research highlights the increasing importance of preserving and disseminating local wisdom, particularly in health contexts, to foster global recognition and academic collaboration. However, a critical problem persists: the lack of a standardized English vocabulary resource for health-related local wisdom, which impedes international communication and limits the accessibility of Thai health knowledge. This qualitative study analyzed 30 articles from the Thai Journal Citation Index (TCI) database using tools such as WordSmith Tool and AntWordProfiler to examine word frequency and vocabulary profiles systematically. The findings reveal that 60.24% of the identified words belong to the first 1,000 most common English words, 9.64% are academic English vocabulary, and 6.66% fall within the second 1,000 most common words, while 23.46% constitute other terms. Key challenges include limited linguistic diversity in corpora, restricted access to community-based local wisdom, and insufficient tools for managing vocabulary data effectively. To address these issues, the study suggests adopting corpus linguistic technologies to enhance data collection and analysis, fostering collaborations among academics and local communities, and developing vocabulary corpora that are applicable locally and globally. These efforts contribute to the creation of a standardized English vocabulary database, facilitating the preservation and international dissemination of health-related local wisdom while supporting academic and intercultural communication.